Description and Ecology of Indonesian Species Tetrastigma glabratum (Blume) Planch, a host of Rafflesiaceae - Lianah, Lianah (Journal of Tropical Crop Science, 2014)
This article presents an overview of the currentknowledge of Tetrastigma glabratum (Blume) Planch, ahost of Rafesiaceae, by providing information onbotany and ecology of T. glabratum, and conservationstatus by propagating the plants vegetatively andmonitoring its growth in-situ and ex-situ. The study wasconducted in the protected rainforests at Mount Prau,Candiroto, North Kedu, Central Java between 2009-2014. Shoot growth and expansion in stem diameterwere faster in-situ than ex-situ whereas the number ofleaves was similar in both locations. Ex-situconservation and cultivation is very important to protectthese rare, unique, and endangered species fromextinction.